2009
DOI: 10.15388/ekon.2009.0.1040
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Institutional Environment on the Economic Development

Abstract: Economic literature recognizes three “deep determinants” of economic development: institutions, geography and openness to trade. Discussion in the literature focuses on what part of the income per capita variation can be explained by institutions, geography and openness to trade. The empirical results can’t offer a clear answer, but there is a broader agreement in the literature that institutions play a more important role than geography and openness to trade. What is unclear whether the institutions also can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Additionally, the adoption of the framework of the developed nations with large urban centers may not be beneficial for the developing countries (Roundy, 2017). Consequently, the regional institutional environment is usually measured through variables such as security of property rights, rule of law, corruption, bureaucratic quality, the size of the market, the availability of capital, accessibility, thickness of input markets, quality of the regional workforce and availability of resources and other institutional variables (Brekke, 2015; Fritsch, 2013; Jankauskas and Seputien, 2009). The selection of such factors which are directly or indirectly related to institutions and can be compared at interstate level is also constrained by the limited and reliable data availability.…”
Section: Institutional Quality/environment Differences Across the Indian Statesmentioning
confidence: 99%
“…Additionally, the adoption of the framework of the developed nations with large urban centers may not be beneficial for the developing countries (Roundy, 2017). Consequently, the regional institutional environment is usually measured through variables such as security of property rights, rule of law, corruption, bureaucratic quality, the size of the market, the availability of capital, accessibility, thickness of input markets, quality of the regional workforce and availability of resources and other institutional variables (Brekke, 2015; Fritsch, 2013; Jankauskas and Seputien, 2009). The selection of such factors which are directly or indirectly related to institutions and can be compared at interstate level is also constrained by the limited and reliable data availability.…”
Section: Institutional Quality/environment Differences Across the Indian Statesmentioning
confidence: 99%
“…-щорічне дослідження групи Всесвітнього банку «Doing Business», спрямоване на оцінку якості інституційного середовища і регулятивних процедур (тобто спирається на концепцію екосистеми підприємництва); наукові дослідження підприємницького середовища, що проводяться науковцями різних країн [6][7][8][9][10];…”
Section: с екція Iunclassified
“…Many authors attribute differences between the growth rates of different economies to their institutional frameworks (Acemoglu et al, 2005;Henderson, 2002;Reynolds et al, 1999;Zacharakis et al, 2000). Economic growth and the development of institutions is a highly interdependent process at the macro level (Aixala and Fabro, 2008;Jankauskas and Seputiene, 2009;Rodrik, 2000). Broadman et al (2004) found that economic growth in the emerging economies of Eastern Europe was impeded by the absence of effective market-based institutions to protect property rights and to ensure fair competition.…”
Section: Informal Institutionsmentioning
confidence: 99%